Pendekatan Pembelajaran Mendalam (Deep Learning Approach) dalam Mengembangkan Kemampuan Berpikir Kritis Siswa pada Pembelajaran IPS Telaah Literatur - Julinda Siregar; Manroni Manroni; Tri Ratna Widiastuti; Lala Komalasari; Lutfiah Aminy; Herni Kurnia; Saruwi Saruwi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This article presents a literature review on the implementation of the deep learning approach in the context of Social Studies (IPS) education, particularly in developing students’ critical thinking skills. Deep learning encourages students to understand concepts comprehensively, connect new information with prior knowledge, and engage in meaningful analysis and reflection. Based on a review of various national and international studies, this approach has been shown to enhance student engagement, conceptual understanding, and higher-order thinking skills. The article also outlines implementation challenges, practical recommendations for teachers, and directions for future research.